California Democratic State Convention pamphlet (1968)
A program booklet for the California Democratic State Convention held in Sacramento on August 10–11, 1968, at the Hotel El Dorado. It includes welcome messages from Pacific Telephone and Charles Warren, chairman of the Democratic State Central Committee, greeting attendees and highlighting local hospitality. The booklet provides a detailed agenda for both the convention and the Democratic State Central Committee meeting, listing speakers such as Attorney General Thomas C. Lynch, Alan Cranston, and Senator Eugene McCarthy. It also features a map of Sacramento and promotes the city as the "Camellia Capital of the World."